USING THE GNU RADIO SOFTWARE PLATFORM FOR THE IMPLEMENTATION OF THE SEARCH ALGORITHM FOR THE CORRELATION INTERFEROMETER DIRECTOR - HULA, IHOR; POLIKAROVSKYKH, OLEKSIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
During the development of modern radio equipment, software and hardware systems SDR (SDR - Software Defined Radio) became widely used. SDR systems, in particular, are used in the design of direction finders of radio signal sources. The effectiveness of direction finding and determination of radio radiation sources is largely determined technical characteristics of the equipment.For modern systems for detecting the location of radio radiation sources, direction finders based on a correlation interferometer, which can perform direction finding of almost all types of radio signals, are best suited. Such direction finders can recognize broadband modulated signals, simultaneously process and recognize several signals in one frequency channel, both from one source of radio signals (coherent) and from several sources (incoherent). A radio receiver using SDR technology can be programmatically reconfigured with the help of software. Such a radio receiver has a broadband radio frequency part with a large dynamic range, a high-speed ADC path, a powerful signal processor and a specialized digital filtering path. SDR receivers can receive signals of various standards and frequencies, the choice of which depends on specific tasks.The most flexible current software platform for SDR systems is the open source software platform GNU RADIO. The article is devoted to consideration of the issue of using the GNU RADIO software platform to implement the search algorithm of the direction finder of the correlation interferometer. The Ettus USRP N210 SDR platform was chosen to implement the direction finder using the correlation interferometer algorithm. In this study, a two-channel software-controlled model of the direction finder, which works according to the correlation interferometer algorithm, was proposed. As a result of measuring the placement angle sources of radio signals, the individual absolute error was about 2 to 4 degrees, while the average absolute error was about 3 degrees. This result is quite good for such mobile phones two-channel systems. Systems with 4 or more channels have higher accuracy, but they have much lower economic profitability.
Keywords: correlation interferometer algorithm; SDR system; GNU RADIO